The Development of Mathematics Learning Methods Through E-Learning Media in SMP Amir Hamzah Medan - Muhammad Arif Hidayat; Marhan Hasibuan (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Islam Malang, 2024)
Maths is one of the least popular subjects in schools. This research aims to develop an e-learning-based method of learning mathematics through a network (computer network). The e-learning method in learning mathematics is intended to deliver a series of learning solutions that can attract learning interest, and increase knowledge and skills. This research is a qualitative study that produces descriptive data with the research subjects being 30 students of SMP Amir Hamzah Medan class IX-b and 1 mathematics teacher who teaches in the class. The instrument analysis technique uses a validity test which is carried out to determine the level of measurement accuracy of an instrument used in a study. The study results are descriptive statistical test results with the ability of the characteristics of medium, high, and low results based on self-assessment and peer assessment. The utilization of e-learning can bring a new atmosphere to the development of learning to the maximum. It can provide benefits such as shortening learning time and making study costs more economical, facilitating interaction between students and materials, students can share information. They can access learning materials at any time and repeatedly.